Pengaruh Variasi Media terhadap Aktivitas Fitase Burkholderia Sp. Strain HF. 7 - Hafsan, Hafsan; Maslan, Muhammad; Masri, Mashuri; Agustina, Laily; Natsir, Asmuddin; Ahmad, Ahyar (Fakultas MIPA UNM, 2019)
Abstract. Â Cereals and legumes used as animal feed containing phytic acid which cannot be absorbed by the digestive tract of monogastric animals because phytic acid (C6H18O24P6) is an antinutrient that binds approximately 80% P in feed, also binds to proteins, vitamins and minerals (Mg++, Fe++, Zn++, Mn++, Ca++). Then, one option to overcome this problem is the application of phytase enzymes from various sources, including those produced by bacteria. Phytase enzymes can hydrolyse phytic acid in the feed. This study was aimed to determine the growth phase of Burkholderia sp. HF.7 and optimisation of production of phytase activity from variations of Phytate Production Media (PPM) media. This research used as a descriptive approach. The study design used a completely randomised design (CRD) with a factorial pattern consisting of 2 factors, each variation in phytate sources: calcium (Ca) phytate, rice bran, corn bran, and soybeans. Nitrogen source: (NH4) 2SO4, yeast extract, and peptone. Burkholderia sp. HF.7 Growth phase as a standard for phytase production is the 62-hour stationary phase with an OD value of 2.060 log/cell. The optimum phytase production in the variation of PPM media is soybean-peptone with a protein content value of 46.5 mg/mL and an activity value of 8.20 U/mL under conditions of pH 7 with incubation of 37oC for 62 hours. So, phytase activity produced by PPM of cereal crops has a higher current value compared to PPM Ca-phytate media with low activity value.Keywords: Burkholderia, Phytate, Phytase, enzymes.